The physics of ferroelectric and antiferroelectric liquid crystals - Musevic, I. (World Scientific, 2000)
In this book the basic physics of ferroelectric liquid crystals is presented in a transparent way together with the linear and non-linear optics of these systems. Specific attention is paid to the applications of ferroelectric liquid crystals as electro-optic modulators, matrix displays, optical logic gates, optical phase conjugation devices, elements for optical computing and erasable optical memories. A special chapter is devoted to polymer ferroelectric liquid crystals.